Quality assessment of a clinical next-generation sequencing melanoma panel within the Italian Melanoma Intergroup (IMI) - Irene Vanni; Milena Casula; Lorenza Pastorino; Antonella Manca; Bruna Dalmasso; Virginia Andreotti; Marina Pisano; Maria Colombino; Italian Association for Cancer Research (AIRC); Ulrich Pfeffer; Enrica Teresa Tanda; Carla Rozzo; et al. (BMC, 2020)
Abstract Background Identification of somatic mutations in key oncogenes in melanoma is important to lead the effective and efficient use of personalized anticancer treatment. Conventional methods focus on few genes per run and, therefore, are unable to screen for multiple genes simultaneously. The use of Next-Generation Sequencing (NGS) technologies enables sequencing of multiple cancer-driving genes in a single assay, with reduced costs and DNA quantity needed and increased mutation detection sensitivity. Methods We designed a customized IMI somatic gene panel for targeted sequencing of actionable melanoma mutations; this panel was tested on three different NGS platforms using 11 metastatic melanoma tissue samples in blinded manner between two EMQN quality certificated laboratory. Results The detection limit of our assay was set-up to a Variant Allele Frequency (VAF) of 10% with a coverage of at least 200x. All somatic variants detected by all NGS platforms with a VAF ≥ 10%, were also validated by an independent method. The IMI panel achieved a very good concordance among the three NGS platforms. Conclusion This study demonstrated that, using the main sequencing platforms currently available in the diagnostic setting, the IMI panel can be adopted among different centers providing comparable results.